Defeat-induced activation of the ventral medial prefrontal cortex is necessary for resistance to conditioned defeat - Morrison, Kathleen E. (2013)
The ventral medial prefrontal cortex (vmPFC) controls vulnerability to the negative effects of chronic or uncontrollable stress. Dominance status alters responses to social defeat in the conditioned defeat model, which is a model characterized by loss of territorial aggression and increased submissive and defensive behavior following an acute social defeat. We have previously shown that dominant individuals show a reduced conditioned defeat response and increased defeat-induced neural activation in the vmPFC compared to subordinates. Here, we tested the hypothesis that defeat-induced activation of the vmPFC is necessary to confer resistance to conditioned defeat in dominants. We paired weight-matched male Syrian hamsters (Mesocricetus auratus) in daily 5-min aggressive encounters for two weeks and identified dominants and subordinates. Twenty-four hours after the final pairing, animals were bilaterally injected with 200 nl of the GABA(A) receptor agonist muscimol (1.1nmol) or 200 nl of saline vehicle 5 minutes prior to social defeat. Defeat consisted of 3, 5-min encounters with resident aggressor hamsters at 10-min intervals. Twenty-four hours following social defeat, animals received conditioned defeat testing which involved a 5-min social interaction test with a non-aggressive intruder. Muscimol injection prior to social defeat prevented the reduced conditioned defeat response observed in vehicle-treated dominants. Further, there was no effect of muscimol injection on the conditioned defeat response in subordinates or controls. These data support the conclusion that activation of the vmPFC during social defeat is necessary for the protective effects of dominant social status on the acquisition of conditioned defeat.